Prox-regularization of the dual method of centers for generalized fractional programs. (4th May 2019) - Boufi, K.; Roubi, A.
Abstract : We present in this paper a prox-dual regularization algorithm for solving generalized fractional programming problems. The algorithm combines the dual method of centres for generalized fractional programs and the proximal point algorithm and can handle nondifferentiable convex problems with possibly unbounded feasible constraints set. The proposed procedure generates two sequences of dual and primal values that approximate the optimal value of the considered problem respectively from below and from above at each step. It also generates a sequence of dual solutions that converges to a solution of the dual problem, and a sequence of primal solutions whose every accumulation point is a solution of the primal problem. For a class of problems, including linear fractional programs, the algorithm converges linearly.